Applying Brazilian front-of-pack nutrition labeling and PAHO nutritional criteria to digital food advertising: regulatory implications for protecting children and adolescents - Juliana de Paula Matos; Breenda Lorranny Santos Gonçalves Araújo; Mariana Ribeiro; Laís Amaral Mais; Paula Martins Horta (PLoS ONE, 2026)
Front-of-pack nutrition labeling (FoPNL) and restrictions on food advertising are regulatory strategies to support informed dietary choices and reduce exposure to unhealthy food. These measures are often integrated through a policy package, that employs a Nutrient Profile Model (NPM) for the classification of food. In Brazil, however, these policies remain fragmented, and current food advertising regulations do not fully cover all channels, particularly digital media. This study applied the NPM adopted in Brazil’s FoPNL (RDC No. 429/2020 in conjunction with IN No. 75/2020, hereafter RDC 429) and those proposed by the Pan American Health Organization (PAHO) for identifying foods subject to advertising restrictions on social media posts directed at children and adolescents. The sample included posts from ultra-processed food brands/products on Instagram (n = 623), TikTok (n = 257), and YouTube (n = 114). Both NPM were applied to assess non-compliance at the food-item level and at the advertisement level (considering posts containing at least one non-compliant food). At the food-item level, 61.28% of products exceeded at least one item of RDC 429, with the highest prevalence on TikTok (72.63%), while 93.86% were non-compliant according to PAHO, reaching 100% on TikTok and 98.5% on YouTube. At the advertisement level, 49.53% of posts contained at least one non-compliant food under RDC 429, and 74.13% under PAHO, with YouTube showing the greatest potential for restriction (62.16% RDC; 99.10% PAHO). Both models are feasible for regulating digital food advertising: the PAHO provides a robust framework, while RDC 429 offers a strategic starting point given its current implementation in Brazil.